2013
DOI: 10.1063/1.4811944
|View full text |Cite
|
Sign up to set email alerts
|

Crystallisation in a granular material

Abstract: Formation of ordered structure and its effect on particle percolation in a vibrated bed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…These results indicate that above a certain value of the particle size ratio, the solid fraction of binary samples does not reach maximum. Solid fractions varied from 0.597 to 0.625 in physical samples which corroborated findings of, inter alia, Chen [33] and Francois et al [34], EDEM Software [32] and Francois et al [34], who reported that for randomly arranged spheres the packing density varied between 57 and 64 %.…”
Section: Numerical Simulationssupporting
confidence: 83%
“…These results indicate that above a certain value of the particle size ratio, the solid fraction of binary samples does not reach maximum. Solid fractions varied from 0.597 to 0.625 in physical samples which corroborated findings of, inter alia, Chen [33] and Francois et al [34], EDEM Software [32] and Francois et al [34], who reported that for randomly arranged spheres the packing density varied between 57 and 64 %.…”
Section: Numerical Simulationssupporting
confidence: 83%